2017
DOI: 10.1245/s10434-017-5891-6
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Surgery: Why Don’t We Let the Guidelines Guide Practice?

Abstract: In the current era of evidence-based medicine, clinical practice guidelines (CPGs), care pathways, and best practice protocols are ubiquitous. CPGs are systematically developed statements, designed to assist clinicians and patients with decisions regarding appropriate care.1 Public health agencies and professional societies tasked with creating these guidelines are faced with the challenge of providing comprehensive, specific, understandable, and clinically usable recommendations. Underlying the tremendous eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Explanations for this non-adherence in general can vary greatly, ranging from lack of familiarity to low outcome expectancy or disagreement 29. For melanoma-specific adherence to guidelines, Kang and Wong and Varey et al30,31 showed that for wide local excisions for melanoma, surgeons with a high melanoma caseload (> 30) were more likely to perform procedures concordant with the guidelines than those with a lower caseload. Another reason might be that Dutch guidelines have only advised on SLNB since 2005, and waited until 2012 to provide a recommendation, which is still not solid advice.…”
Section: Discussionmentioning
confidence: 99%
“…Explanations for this non-adherence in general can vary greatly, ranging from lack of familiarity to low outcome expectancy or disagreement 29. For melanoma-specific adherence to guidelines, Kang and Wong and Varey et al30,31 showed that for wide local excisions for melanoma, surgeons with a high melanoma caseload (> 30) were more likely to perform procedures concordant with the guidelines than those with a lower caseload. Another reason might be that Dutch guidelines have only advised on SLNB since 2005, and waited until 2012 to provide a recommendation, which is still not solid advice.…”
Section: Discussionmentioning
confidence: 99%